Islamic Integrated Curriculum Model to Strengthen Santri’s Religious Character: A Case Study at Islamic Boarding School in Blitar - Aziz, Abd.; Setyawan, Bagus Wahyu; Purwowidodo, Agus; Yasin, Muhamad (IAIN Ponorogo, 2023)
The religion-based integrated curriculum model differs the curriculum system at Islamic boarding schools from other formal schools. Thus, the researchers conducted a case study to determine the Islamic integrated curriculum model at Islamic boarding schools in Blitar. The sample of this research was five leading Islamic boarding schools in Blitar. The data were collected through field observation and in-depth interviews with some informants, such as ustadz/ustadzah, santri, and santri’s guardians/parents. Then, it was analyzed using integrative and interactive techniques. It included data reduction, data display, and conclusion. This study found that the Islamic integrated curriculum system was applied by combining the national curriculum with the hidden curriculum compiled by each Islamic boarding school. It was adjusted to the Islamic boarding school’s vision, mission, and form. Applying the Islamic integrated curriculum model has effectively improved the santri’s religious character. Besides, the parent/guardian satisfaction index showed 89.6%. This research contributes to the Islamic integrated curriculum model into santri’s religious character in Blitar, East Java, Indonesia.